2013
DOI: 10.1017/s1368980013002565
|View full text |Cite
|
Sign up to set email alerts
|

A population-based dietary inflammatory index predicts levels of C-reactive protein in the Seasonal Variation of Blood Cholesterol Study (SEASONS)

Abstract: Objective To perform construct validation of the population-based Dietary Inflammatory Index (DII) using dietary data from two different dietary assessments and serum high-sensitivity C-reactive protein (hs-CRP) as the construct validator. Design Using data derived from (i) three 24 h dietary recalls (24HR) at baseline and at the end of each subsequent quarter (i.e. up to fifteen over a year) and (ii) a 7 d dietary recall (7DDR) measured at baseline and then quarterly, regression analyses were conducted to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
675
12
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 572 publications
(744 citation statements)
references
References 69 publications
26
675
12
7
Order By: Relevance
“…Forty-five food parameters, including foods, nutrients, and other bioactive compounds were evaluated based on their inflammatory effect on some specific inflammatory markers, such as interleukin (IL)-1, IL-4, IL-6, IL-10, tumor necrosis factor (TNF)-a, and CRP. The DII has been validated demonstrating its effectiveness in predicting serum CRP levels in a large longitudinal epidemiological study (Shivappa et al 2014c). Previously, we observed that women with a pro-inflammatory diet (higher DII scores) had a higher risk of developing CRC in a US-based cohort study (Shivappa et al 2014a).…”
Section: Introductionmentioning
confidence: 84%
“…Forty-five food parameters, including foods, nutrients, and other bioactive compounds were evaluated based on their inflammatory effect on some specific inflammatory markers, such as interleukin (IL)-1, IL-4, IL-6, IL-10, tumor necrosis factor (TNF)-a, and CRP. The DII has been validated demonstrating its effectiveness in predicting serum CRP levels in a large longitudinal epidemiological study (Shivappa et al 2014c). Previously, we observed that women with a pro-inflammatory diet (higher DII scores) had a higher risk of developing CRC in a US-based cohort study (Shivappa et al 2014a).…”
Section: Introductionmentioning
confidence: 84%
“…A higher DII score indicates a more pro-inflammatory diet, which included all possible food/ nutrients listed on the food frequency questionnaire. A validation of the DII score, based on both dietary recalls and a structured questionnaire (the seven-day dietary recall), similar to a food frequency questionnaire, has been published elsewhere [16]. A flow chart of the DII methodology is depicted in Fig.…”
Section: The Dietary Inflammatory Index (Dii)mentioning
confidence: 99%
“…Higher DII scores indicate more proinflammatory diets. The DII scoring system has been validated with various inflammatory markers, including CRP [16] and interleukin-6 [17].…”
mentioning
confidence: 99%
“…DII has been shown to be predictive of levels of various inflammatory markers (Cavicchia et al 2009;Shivappa et al 2014b;Shivappa et al 2015b). DII can be used to evaluate the dietary inflammatory potential in D r a f t different populations using a variety of assessment instruments such as 24-hour recall interviews, food frequency questionnaires (FFQ) and food record (Shivappa et al 2014a;Shivappa et al 2014b;Wirth et al 2014;Wood et al 2015). …”
Section: Introductionmentioning
confidence: 99%